Upper respiratory tract infection and mucosal immunity in young ice hockey players during the pretournament training period - Orysiak, J.; Witek, K.; Malczewska-Lenczowska, J.; Zembron-Lacny, A.; Pokrywka, A.; Sitkowski, D. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to determine the effects of 17 days of training during preparation for the Ice Hockey Under 18 World Championship of the Polish ice hockey national team on the mucosal immune function and monitor upper respiratory tract infection (URTI) incidence before, during, and after the competition. Twelve male ice hockey players (age, 17.7 ± 0.5 years) were recruited for this study. The first saliva and blood collection took place at the beginning of the training camp (without training at the training camp), the second one was collected on the 9th day of the training camp immediately after the intensification of training, and the third collection was performed on the 13th day of training (4 days before leaving for the World Championship) in the tapering phase. To assess the mucosal immune function, concentrations of secretory immunoglobulin A (sIgA), sIgA1, and sIgA2 were analyzed in saliva. Cortisol concentration and creatine kinase activity were determined in blood, as indicators of stress and muscle damage, respectively. The Wisconsin Upper Respiratory Symptom Survey-21 questionnaire was used to assess URTI symptoms. A significant increase in the sIgA1 and sIgA2 concentrations was observed in the third collection compared with the second time point (114.45 ± 33.00 vs. 77.49 ± 27.29 and 88.97 ± 25.33 vs. 71.65 ± 32.44 U, respectively). There were no statistically significant correlations between the URTI incidence and saliva variables. In conclusion, the tapering period positively affects the mucosal immune function, especially sIgA1 and sIgA2 concentrations, with no significant change in the frequency of URTI in young ice hockey players.